The ethics of belief and beyond understanding mental normativity - Schmidt, Sebastian 1981-; Ernst, Gerhard 1971- (Routledge studies in epistemology, 2020)
"This volume provides a framework for approaching and understanding mental normativity. It presents cutting-edge research on the ethics of belief as well as innovative research beyond the normativity of belief-and towards an ethics of mind. By moving beyond traditional issues of epistemology the contributors discuss the most current ideas revolving around rationality, responsibility, and normativity. The book's chapters are divided into two main parts. The first part discusses contemporary issues surrounding the normativity of belief. The essays here cover topics such as control over belief and its implication for the ethics of belief, the role of the epistemic community for the possibility of epistemic normativity, responsibility for believing and responsivity to reasons, the structure and content of epistemic norms, and evidentialism and pragmatism. In Part II the focus shifts from the practical dimensions of belief to the normativity and rationality of other mental states-especially blame, passing thoughts, fantasies, intentions, decisions, and emotions. These essays illustrate how we might approach an ethics of mind by focusing not only on belief, but also on debates about intention, the rationality of emotion, and involuntary mental states. The Ethics of Belief and Beyond paves the way towards an ethics of mind by building on and contributing to recent philosophical discussions in the ethics of belief and the normativity of other mental phenomena. It will be of interest to upper-level students and researchers working in epistemology, ethics, philosophy of action, philosophy of mind, and moral psychology"--